2020
DOI: 10.1001/jama.2020.6940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Glucose Monitoring on Glycemic Control in Adolescents and Young Adults With Type 1 Diabetes

Abstract: ; for the CGM Intervention in Teens and Young Adults with T1D (CITY) Study Group IMPORTANCE Adolescents and young adults with type 1 diabetes exhibit the worst glycemic control among individuals with type 1 diabetes across the lifespan. Although continuous glucose monitoring (CGM) has been shown to improve glycemic control in adults, its benefit in adolescents and young adults has not been demonstrated. OBJECTIVE To determine the effect of CGM on glycemic control in adolescents and young adults with type 1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
221
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 295 publications
(229 citation statements)
references
References 17 publications
4
221
1
3
Order By: Relevance
“…Results of previous research on the benefits of CGM for adolescents has been mixed. In a recent randomized controlled trial, a significant reduction in HbA1c by 0.37% was found among adolescents with the use of adjunctive CGM 40 . In prior research, when data from children and adolescents were analyzed together with a larger adult population, CGM use was associated with reduction in HbA1c 11,41,42 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results of previous research on the benefits of CGM for adolescents has been mixed. In a recent randomized controlled trial, a significant reduction in HbA1c by 0.37% was found among adolescents with the use of adjunctive CGM 40 . In prior research, when data from children and adolescents were analyzed together with a larger adult population, CGM use was associated with reduction in HbA1c 11,41,42 .…”
Section: Discussionmentioning
confidence: 97%
“…In a recent randomized controlled trial, a significant reduction in HbA1c by 0.37% was found among adolescents with the use of adjunctive CGM. 40 In prior research, when data from children and adolescents were analyzed together with a larger adult population, CGM use was associated with reduction in HbA1c. 11,41,42 Our findings showing a negative association between SMBG and bolus frequency and HbA1c are supported by several studies examining insulin pump self-management in this population.…”
Section: Hospitalizations and Ed Visits Across Hba1c Groupsmentioning
confidence: 99%
“…S everal studies have shown use of continuous glucose monitors (CGMs) can improve glycemic control and reduce hypoglycemia for participants with type 1 diabetes (T1D). [1][2][3] The DIAMOND T1D trial found that participants randomized to receive a real-time continuous glucose monitor (rtCGM) had a 0.6% greater reduction in mean hemoglobin A1c (HbA1c) and spent an additional 77 min per day in range 70-180 mg/dL compared with participants in selfmonitoring of blood glucose (SMBG) group. 4 Beyond the finding of a clinically relevant overall benefit of rtCGMs, it is important to assess improvement at an individual level to identify individuals who can potentially benefit the most from rtCGM use.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JAMA, 2 clinical trials provide important data on the efficacy of CGM in these high-risk populations with type 1 diabetes. 5,6 The periods of adolescence and young adulthood (13-24 y) are distinctive developmental stages marked by transition of disease self-management tasks from family to self in the midst of tumultuous change in an individual's social, geographic, financial, and health care situations. 7 As a result, adolescents and young adults exhibit the highest hemoglobin A 1c (HbA 1c ) levels and rates of hospitalization of all age groups with type 1 diabetes.…”
mentioning
confidence: 99%